2001
DOI: 10.1093/geront/41.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Come Talk With Me

Abstract: Nursing staff can be trained to improve and maintain communication skills during care without increasing the amount of time delivering care. The methodological advantages of including measures to assess treatment implementation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(57 citation statements)
references
References 39 publications
1
56
0
Order By: Relevance
“…Communication partner training can increase the likelihood and frequency of successful interactions with communication-impaired individuals. 43,46,49,52,53 A randomized controlled trial evaluated the effect of a nurse training program that emphasized psychosocial caring behaviors such as attention, eye contact, touch, and treating the ICU patient as a person. 42 In general, positive behaviors increased and negative behaviors decreased for both nurses and patients following nurse training ( p ≤ .04).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication partner training can increase the likelihood and frequency of successful interactions with communication-impaired individuals. 43,46,49,52,53 A randomized controlled trial evaluated the effect of a nurse training program that emphasized psychosocial caring behaviors such as attention, eye contact, touch, and treating the ICU patient as a person. 42 In general, positive behaviors increased and negative behaviors decreased for both nurses and patients following nurse training ( p ≤ .04).…”
Section: Discussionmentioning
confidence: 99%
“…The 80% threshold is commonly acceptable inter-rater agreement in observational coding from videos. 42,4749 Secondly, all videos were reviewed by 2 raters, a primary and secondary rater, before finalizing. Finally, a stratified random sample of 10% of video recordings representing all phases was independently assessed by an external, PhD prepared reviewer who was experienced in coding nonverbal communication and blinded to phase assignment.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a clinician steeped in the restorative tradition might retrain a series of forgotten names until the patient achieves mastery. In contrast, compensatory stimulation strategies often forego direct intervention in favor of external memory aids, caregiver communication strategies (e.g., asking yes/no questions rather than open-ended questions), and structured environmental cues (Bourgeois, Dijkstra, Burgio, & Allen-Burge, 2001; Burgio et al, 2001). The restorative and compensatory traditions both have relative merits.…”
Section: Distinct Philosophical Approaches To Dementia Treatmentmentioning
confidence: 99%
“…The use of financial incentives may only be effective in some service and professional contexts (eg, we found that evidence in support of financial incentives mostly related to North America and European care settings20 53 54). In thinking about workforce development incentives, there may be a need to tailor them and make them relevant to the support workers:51Trained CNAs received public recognition for meeting job performance criteria … by having their names posted weekly on a CNA Honor Roll. All honor-roll CNAs listed were entered into a performance- based lottery held once each week for day and evening shifts (Reid, Parsons, & Green, 1989).…”
Section: Resultsmentioning
confidence: 99%